Sosialisasi Kearifan Lokal Budaya Melayu Lewat Pantun dan Kegiatan Mewarnai Rumah Adat Melayu: Pengabdian - Salhe Ntasia Sitorus; Putri Cahyati; Dwi Rosalinda; Lola Novia Ayuni; Refazatun Nafisa; Chelia Bestari Manik; Ely Kusuma; Aulia Indri Putri Anggraini; Nadine Alya Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Local wisdom is a vital part of national cultural identity that must be introduced from an early age. Malay culture, particularly in Riau Province, embodies noble values reflected in oral traditions such as pantun and material culture like traditional houses. This study aimed to enhance children's cultural awareness and character values (ages 6–11) through an educational and participatory approach involving pantun reading and traditional house coloring activities. The program was held in Kampung Damai Residential Area, Pekanbaru, involving approximately 20 children. A descriptive qualitative method was used, supported by participatory observation and informal interviews. The results showed increased cultural understanding, creativity, and enthusiasm among children toward Malay heritage. The fun and visual approach effectively fostered cultural values while strengthening a sense of pride in local identity. This activity demonstrates that local cultural education can be effectively and enjoyably delivered when adapted to the developmental characteristics of young learners.